2015
DOI: 10.1007/s10661-015-4445-2
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the potential health risk of aluminum and heavy metals in tea leaves and tea infusion of commercially available green tea in Jiangxi, China

Abstract: Heavy metals and Al in tea products are of increasing concern. In this study, contents of Al, Cd, Co, Cr, Cu, Ni, and Pb in commercially available green tea and its infusions were measured by ICP-MS and ICP-AES. Both target hazard quotient (THQ) and hazard index (HI) were employed to assess the potential health risk of studied metals in tea leaves and infusions to drinkers. Results showed that the average contents of Al, Cd, Co, Cr, Cu, Ni, and Pb in tea leaves were 487.57, 0.055, 0.29, 1.63, 17.04, 7.71, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
41
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 39 publications
10
41
5
Order By: Relevance
“…One study reported lead concentrations in liquid coffee of 2.37 and 2.57 μg/L (Ong 2014), and another study reported lead concentrations below the limit of detection of 1.5 μg/L (Ashu and Chandravanshi 2011). Additionally, studies have reported lead in tea leaves or residues from tea infusions of 0.046 to 15.479 μg/g (Li et al 2015;Shekoohiyan et al 2012;Shokrzadeh et al 2008;Onianwa et al 1999;Othman 2010;Al-Othman et al 2012;Zheng et al 2014). Although we did not detect any lead in our direct tap water or boiled tap water control samples, the presence of lead in drinking water is a known concern, as shown by the recent state of emergency issued in Flint, Michigan, because of its drinking water lead content.…”
Section: Discussioncontrasting
confidence: 61%
“…One study reported lead concentrations in liquid coffee of 2.37 and 2.57 μg/L (Ong 2014), and another study reported lead concentrations below the limit of detection of 1.5 μg/L (Ashu and Chandravanshi 2011). Additionally, studies have reported lead in tea leaves or residues from tea infusions of 0.046 to 15.479 μg/g (Li et al 2015;Shekoohiyan et al 2012;Shokrzadeh et al 2008;Onianwa et al 1999;Othman 2010;Al-Othman et al 2012;Zheng et al 2014). Although we did not detect any lead in our direct tap water or boiled tap water control samples, the presence of lead in drinking water is a known concern, as shown by the recent state of emergency issued in Flint, Michigan, because of its drinking water lead content.…”
Section: Discussioncontrasting
confidence: 61%
“…The leached heavy metals and other contaminants are transported to soil and water, leading to the degradation of soil and water quality (Hu MH et al 2014;Lu C 2016;Jingyong L et al 2006;Xiaojuan S et al 2012;Zhang GY et al 2011;Zhang L et al (2014). In addition, crops that grow in the local soil become polluted through their absorption of more toxic elements from contaminated soils and water; this is harmful to human health if the contaminated crops are eaten (Li LH et al 2015). Heavy metals are not degradable and persist in the environment (Islam MN et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the contents of these elements in tea were generally below the maximum permissible limits stipulated by the World Health Organization (WHO) and the United States Pharmacopeia (USP) [212]. In addition, both the target hazard quotient (THQ) and hazard index (HI) levels regarding these elements in certain teas were far below 1, indicating that tea consumption would not increase health risks [214,225]. Besides, the THQ and HI values would decrease as the infusion time increased, so it was suggested to discard the first tea infusion and consume the later ones [214].…”
Section: Potential Safety Issuesmentioning
confidence: 99%
“…Notes: ALP, alkaline phosphatase; ALT, alanine aminotransferase; AST, aspartate transaminase; BMI, body mass index; CAT, catalase; GPx, glutathione peroxidase; GR, glutathione reductase; GSH, reduced glutathione; HbA1c, glycated hemoglobin A1C; HDL-C, high-density lipoprotein-cholesterol; IL, interleukins; LDL-C, low-density lipoprotein-cholesterol; MDA, malonaldehyde; NF-κB, nuclear factor-κB; PPAR γ, peroxisome proliferator-activated receptor γ; SIRT1, sirtuin 1; SLE, systemic lupus erythematosus; SOD, superoxide dismutase; T2DM, type II diabetes mellitus; TC, total cholesterol; TG, triglyceride. Many elements have been detected in tea, including plumbum (Pb), cadmium (Cd), copper (Cu), cobalt (Co), chromium (Cr), nickel (Ni), manganese (Mn), aluminum (Al), arsenic (As), and fluorine (F) [212,214,225]. Some elements, such as Pb and Cd, are toxic, and others, such as Cu and F, are essential elements, but they can be harmful at high levels.…”
Section: Potential Safety Issuesmentioning
confidence: 99%